2008
DOI: 10.1097/dad.0b013e3181651511
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Features in Vitiligo

Abstract: Nevus depigmentosus is a congenital disorder characterized by a nonprogressive hypopigmented lesion, which may not be apparent at birth. Thus, it is sometimes difficult to differentiate vitiligo from nevus depigmentosus only by clinical features. We postulated that the histologic changes in lesional and perilesional skin might be different in the 2 conditions. We took biopsies from both lesional and perilesional skin of 100 cases of vitiligo to assess the number of melanocytes, the amount of melanin, dermal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 14 publications
3
35
1
2
Order By: Relevance
“…Previous studies have shown that histamine stimulates melanocyte proliferation and melanogenesis in vitro [24,25,26,27,28,29,30,31,32]. We now show here that topical histamine consistently induces repigmentation in stable, nonsegmental vitiligo in humans, in parallel with increased melanin indices in histamine-treated normal mouse skin.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that histamine stimulates melanocyte proliferation and melanogenesis in vitro [24,25,26,27,28,29,30,31,32]. We now show here that topical histamine consistently induces repigmentation in stable, nonsegmental vitiligo in humans, in parallel with increased melanin indices in histamine-treated normal mouse skin.…”
Section: Discussionsupporting
confidence: 55%
“…Because prior studies have shown that histamine stimulated melanogenesis via H2r in vitro [30,31,32], we next determined whether topical histamine increases the melanin index via H2r in vivo. We measured the melanin index in mouse ears cotreated with histamine and an H2r antagonist, cimetidine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As poorly functioning melanocytes have been isolated from lesional vitiligo skin and cultured in vitro, [48][49][50][51] the deterioration of melanocyte function may be an early and crucial event in vitiligo. We found that miR-25 downregulated the expression of TYR, TYRP1 and TYRP2, as well as tyrosinase activity in melanocytes, thus impairing melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…12% der Patienten noch einzelne Melanozyten, während vollständig depigmentierte Areale in der Regel keine epidermalen Melanozyten aufweisen [14]. Follikuläre Melanozyten sind in vielen Fällen noch vorhanden (.…”
Section: Histologieunclassified